Planning and Evaluating Science Video Programs Using Communication Science - Joseph Cone; Kirsten Winters (Journal of Applied Communications, 2013)
Science-based videos could be of greater benefit to viewers if video producers understand what decisions and actions these audiences may be considering that can be affected by the videos. Such understanding may be developed through interviews, focus groups, and surveys, which should provide guidance for elements of both the style and content of the video production. The success of the videos in assisting viewers’ understanding and decision making should then be evaluated, for example through surveys, as described here. Following such a process may increase the effectiveness of such videos, thereby also improving the return on the producer’s investment in personnel, time, and other resources. For example, the results of climate change video evaluations presented here do indicate that members of the populations for whom the videos were intended rated them highly, obtained information they considered useful from the videos and were influenced to act on the concerns they had relating to the science topic (climate change risks).
Keywords: video; evaluation; decision-making; communication; climate change